Tai Chi as a rehabilitation method for patients with Parkinson’s disease - Dziarkowski, Dariusz; Białkowska, Aleksandra; Budziejko, Blanka; Cywińska, Oliwia; Gawrych, Szymon; Kurtyka, Daria; Różański, Gracjan; Dobosiewicz, Anna Maria; Badiuk, Nataliia (Journal of Education, Health and Sport, 2018)
Parkinson's disease is the second most common neurodegenerative disease. It belongs to the group of extrapyramidal system diseases. Nowadays it is an incurable disease, not yet examined in its entirety. With the current state of knowledge it is not possible to fully cure this disease, but it is possible to reduce the severity of the symptoms of this disease. Pharmacological treatment, surgical treatment and broadly understood physiotherapy, including Tai Chi, are the methods of treatment used in the fight against Parkinson's disease. Thanks to these methods, there is a chance to significantly reduce the severity of the symptoms characteristic of this disease, i.e. muscle tension, balance and coordination disorders. The incidence of this disease increases with age, and it is most common for people over the age of sixty. It affects men twice as often. The essence of the disease is a disorder in the number of neurons in which dopamine is produced, more precisely in the compact part of the black creature. This causes disturbances in the transmission of information in the central nervous system, which results in three basic symptoms: hypertonia, akinesis and tremor. In the treatment of these symptoms an important role is played by rehabilitation, one of the elements of which is Tai Chi. In the latest scientific reports there are many studies evaluating the influence of Tai Chi on the reduction of symptoms in Parkinson's patients.